Early maladaptive schemas as predictors of depressive symptoms and treatment success in an outpatient rehabilitation sample - Schosser, Alexandra; Fischer-Hansal, Daniela; Traugott-Suchomel, Miriam; Senft, Birgit (Frontiers in Psychiatry, 2026)
Background and objectivesEarly maladaptive schemas (EMSs) are cognitive–emotional patterns linked to depression. Their role in psychiatric rehabilitation and treatment success remains unclear. This study examines the association between EMSs and depressive symptom severity at admission and its impact on treatment outcomes.Materials and methodsA total of 2,568 patients in a 6-week outpatient psychiatric rehabilitation program in Austria were assessed. EMSs were measured using the Young Schema Questionnaire-Short Form 3 (YSQ-S3), and depressive symptoms were measured using the Beck Depression Inventory-Second Edition (BDI-2). Multiple regression analyses determined the predictive value of EMSs on symptom severity and treatment response. Cluster analyses identified schema profiles and their relation to treatment success.ResultsHigher EMS scores, especially in Disconnection/Rejection and Impaired Autonomy/Performance, correlated with higher depression levels at admission. Regression models explained 46% of symptom variance. However, EMSs had limited predictive value for treatment success, with small effects for Dependence/Incompetence and Subjugation. Cluster analyses showed that patients with high EMSs had more severe symptoms but similar clinical improvement.DiscussionEMSs showed a significant influence on the severity of depressive symptoms at admission. However, their impact on treatment success was limited; namely, similar clinical improvement was found in patients with high EMSs.